Cell salvage techniques and obstetric haemorrhage - Hashviniya Sekar; Wasim Lodhi; Wai Yoong (Taylor & Francis Group, 2024)
Over the last decade, the incidence of postpartum haemorrhage has risen because of increasing maternal age at time of delivery, multiple births, obesity and increased obstetric interventions, resulting in most of these women requiring blood transfusions. While lifesaving, blood transfusion is not without risk. Recipients may rarely develop transfusion-transmitted infections or suffer immunological sequelae. Intraoperative cell salvage is recommended by several national policy making organisations as a safe cost-effective alternative to autologous blood transfusion in both emergency and elective settings. Moreover, emerging data has also revealed that autotransfusion of vaginally shed blood is both feasible and safe. These techniques are useful in patients who decline blood transfusions for both personal and religious reasons and should therefore be taken into consideration when planning place of birth.